Pan-immune inflammation value: A novel biomarker for cataract - Chuan-Xi Wang; Jia-Wei Fan; Jing-Hui Liu; Si-Yu Lin; Jing-Jing Hou; Zheng-Xuan Jiang; Jie Gao (PLoS ONE, 2025)
Background Inflammation significantly contributes to cataract formation; Pan-immune inflammation value (PIV) is an emerging marker that may reflect systemic inflammation. This study aimed to explore the connection between PIV and cataract formation. Methods We analyzed 8,235 participants from the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2008. PIV was log-transformed, and weighted logistic regression, restricted cubic splines (RCS), subgroup, and sensitivity analyses were performed to evaluate associations. The receiver operating characteristic (ROC) curves were used to assess predictive performance. Results Cataract prevalence was 6.6%. Higher ln-PIV was positively associated with cataract prevalence [OR=1.35, 95%CI: 1.08–1.69, P = 0.015]. The association was linear, consistent across subgroups, and robust in sensitivity analyses. The ROC analysis indicated that PIV had better predictive ability for cataract than other inflammatory indices. Conclusion We found that higher PIV levels were positively associated with cataract prevalence, which highlights the value of inflammatory markers in assessing cataract development and provides new ideas for the clinical detection of cataracts.